A Bibliometric Study on Digital Entrepreneurship: Mapping the Evolutions and Its Impact on Startups - Loso Judijanto; Ferry Arfiansyah (West Science Journal Economic and Entrepreneurship, 2024)
This study presents a bibliometric analysis of digital entrepreneurship, mapping its evolution, key themes, and impact on startups. Utilizing data from peer-reviewed publications from 2005 to 2025, the research highlights a significant surge in scholarly interest, particularly post-2015, driven by advancements in digital technologies and their implications for entrepreneurship. The analysis identifies central themes such as "digital platforms," "innovation," and "electronic commerce," while also emphasizing the growing importance of digital skills and funding mechanisms like crowdfunding. The geographical distribution of research contributions reveals a global phenomenon, with major insights emerging from countries such as the United States, the United Kingdom, and Australia, alongside rising participation from emerging markets like Vietnam and India. The study underscores the necessity for ongoing research to address the challenges posed by rapid technological change and ethical considerations, while advocating for interdisciplinary collaboration to enrich the understanding of digital entrepreneurship. This research serves as a valuable resource for scholars, practitioners, and policymakers, providing insights into the transformative potential of digital entrepreneurship in today’s economy.